2003
DOI: 10.1046/j.1365-2842.2003.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis, caries and salivary factors in Sjögren's syndrome patients compared to sex‐ and age‐matched controls

Abstract: The aims of this investigation were: (i) to study a group of dry mouth Sjögren's syndrome (SS) patients comprising individuals with pathological and non-pathological amounts of rest saliva and (ii) to compare these two categories of SS patients with a sex- and age-matched control group with respect to their periodontal and dental status. Thirty-three dry mouth patients and 33 sex- and age-matched patients, referred to the same private dental clinic in southern Norway, were examined for rest and stimulated sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…However, several recent studies corroborate this thesis. [9][10][11][12][13] Antoniazzi et al 14 studied the major inflammatory markers in gingival crevicular fluid and major indices in participants with primary SS (SSp) and secondary SS (SSs). Individuals with SSs demonstrated a significantly lower stimulated whole saliva flow rate and higher mean plaque index, gingival index, probing depth, clinical attachment level, and bleeding on probing than controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies corroborate this thesis. [9][10][11][12][13] Antoniazzi et al 14 studied the major inflammatory markers in gingival crevicular fluid and major indices in participants with primary SS (SSp) and secondary SS (SSs). Individuals with SSs demonstrated a significantly lower stimulated whole saliva flow rate and higher mean plaque index, gingival index, probing depth, clinical attachment level, and bleeding on probing than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated higher plaque index, gingival bleeding, probing depth, and periodontal index in SS patients with elevated risk of periodontal disease (Najera et al , ; Celenligil et al , ; Rhodus and Michalowicz, ; Ergun et al , ). While others have shown non‐significant differences between SS patients and control groups regarding clinical parameters and periodontal status (Tseng et al , ; Tseng, ; Mutlu et al , ; Lundstrom and Lindstrom, ; Tervahartiala et al , ; Kolavic et al , ; Boutsi et al , ; Kuru et al , ; Jorkjend et al , ; Leung et al , ). In addition, no increased risk of periodontal disease has been detected in some of the above‐mentioned studies (Pedersen et al , ).…”
Section: Periodontal Diseasementioning
confidence: 97%
“…Recently published classification criteria for primary Sjogren’s syndrome by the American College of Rheumatology and the Sjogren’s International Collaborative Clinical Alliance Cohort [7 ■■ ] will facilitate more accurate descriptions of Sjogren’s prevalence, a condition with considerable impact on overall healthrelated quality of life [8 ■ ,9 ■ ]. Whether secondary Sjogren’s in rheumatoid arthritis is associated with an increased periodontal disease remains unclear; some studies [1012] have suggested increased periodontal disease and gingivitis in Sjogren’s, but others have not.…”
Section: Oral Health In Rheumatoid Arthritismentioning
confidence: 99%